Radical Prostatectomy, Sparing of the Seminal Vesicles, and Painful Orgasm. (19th February 2013) - Mogorovich, Andrea; Nilsson, Andreas E.; Tyritzis, Stavros I.; Carlsson, Stefan; Jonsson, Martin; Haendler, Leif; Nyberg, Tommy; Steineck, Gunnar; Wiklund, N. Peter
Abstract: Introduction: Erectile dysfunction has been widely investigated as the major factor responsible for sexual bother in patients after radical prostatectomy (RP); painful orgasm (PO) is one element of this bother, but little is known about its prevalence and its effects on sexual health. Aim: This study aims to investigate the prevalence of PO and to identify potential risk factors. Main Outcome Measures: A total of 1, 411 consecutive patients underwent open (radical retropubic prostatectomy) or robot‐assisted laparoscopic RP between 2002 and 2006. The patients were asked to complete a study‐specific questionnaire. Methods: Of a total of 145 questions, 5 dealt with the orgasmic characteristics. The questionnaire was also administered to a comparison group of 442 persons, matched for age and area of residency. Results: The response rate was 91% (1, 288 patients). A total of 143 (11%) patients reported PO. Among the 834 men being able to have an orgasm, the prevalence was 18% vs. 6% in the comparison group (relative risk [RR] 2.8, 95% confidence interval [CI] 1.7–4.5). When analyzed as independent variables, bilateral seminal vesicle (SV)‐sparing approach (RR 2.33, 95% CI 1.0–5.3, P = 0.045) and age <60 years were significantly related to the presence of PO (95% CI 0.5–0.9, P = 0.019). After adjustment for age, bilateral SV‐sparing still remained a significant predictor for occurrence of PO. Conclusions: We found that PO occurs significantly more often in patients undergoing bilateral SV‐sparing RP when compared with age‐matched comparison population.